KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA GURU SMP NEGERI 2 SAMBAS - Nurainun, Nurainun; Sukmawati, Sukmawati; Wahyudi, Wahyudi (Universitas Tanjungpura, 2023)
This study aims to determine the implementation of the principal's leadership in increasing teacher motivation at SMP Negeri 2 Sambas. This form of research uses qualitative methods. There were 4 research subjects, namely the 51-year-old male headmaster, 58-year-old female vice principal for curricula, 39-year-old female teacher, and 42-year-old female teacher. Methods of data collection by interviews, documentation, and observation. Data analysis uses data reduction, data display and verification. Data validity checking techniques with triangulation tests and member checks. The result of this study is that the leadership of the head of SMP Negeri 2 Sambas in increasing teacher motivation is well implemented. It can be seen from the strategy implemented by the principal in an effort to increase the motivation of teachers at school. The conclusions from this study, namely: (1) the leadership of school principals in increasing teacher work motivation can be done through: formulating visions, building expectations, encouraging efficient use of time, utilizing various learning resources, monitoring student progress, and conducting evaluations, (2) the principal increases the teacher's work motivation in terms of: responsibility, considering risk, feedback, innovative creativity, and the desire to be the best, and (3) supporting and inhibiting factors can come from internal and external factors. The implication of this research is that the leadership applied by the principal is successful in increasing teacher motivation.